PERENCANAAN PEMBANGUNAN DI DESA PETTA TIMUR KECAMATAN TABUKAN UTARA KABUPATEN KEPULAUAN SANGIHE - TADETE, NUR AISIAH; ROMPAS, WELSON; RURU, JOORIE MARHAEN (JURNAL ADMINISTRASI PUBLIK, 2019)
Mature and planning development is one of the important aspects which is also a benchmark forthe progress of a country through village development planning is the initial step to determine the goals forvillage progress and independence. This study aims to determine the development planning in petta villageeast tabukan subdistrict north of sangihe island regency. The method used in this research is a descriptivequalitative method with the inductive approach. Qualitative descriptive research with an inductive approach isa method that illustrates the problem or case that is based on the facts that are based on specific facts andthen examined to solve the problem and draw conclusions generally. Researchers used five indicatorsnamely determining goals, develop the premise (opinion), determine alternative-alternative actions andevaluate this alternative, choose one of the best alternatives, implement a plan and evaluate the results.Based on the results of research conducted that village development planning has not fully gone well. Thisis seen in physical development (community needs) and non-physical development as a whole has not gonewell, yet there are still many community needs that have not been met.Keywords : Planning, Development, Village.